PEMBERDAYAAN USAHA EKONOMI PRODUKTIF BAGI MASYARAKAT MISKIN DI KECAMATAN MRANGGEN: EMPOWERMENT OF PRODUCTIVE ECONOMIC ENTERPRISES FOR POOR COMMUNITIES IN MRANGGEN DISTRICT - Karsiati; Maskudi; Bahri, Saiful; Arwani, Mokhamad (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This community service program aims to empower productive economic businesses for poor communities in Mranggen District. Through various activities, this program focuses on identifying problems faced by economically disadvantaged community groups. The approach implemented includes training, guidance and mentoring in order to develop entrepreneurial skills, as well as identifying relevant business opportunities in the region. Apart from that, this program also seeks to improve existing business management so that it is more efficient and has a positive impact on increasing family income. With this approach, this community service program aims to make a real contribution to reducing poverty levels and improving the welfare of the community in Mranggen District, as well as encouraging sustainable economic development in the region.